HI analysis of resolved galaxies in the MeerKAT Absorption Line Survey - Maina, Eric Kamau (Rhodes University, Faculty of Science, Department of Physics and Electronics)
This doctoral thesis examines two galaxy groups, Klemola 31 and UGC439, leveraging the observational capabilities of the MeerKAT Absorption Line Survey (MALS). The focus was on studying the interstellar medium, specifically the neutral hydrogen (H i) content, distribution, density, and dynamics, through high spatial resolution observations of these groups, and therefore offering insights into the complex processes affecting galaxy evolution in different environments. To make use of an additional tool, the absorption line characteristics of Hi in the two observed systems were analysed and compared with the kinematics and the morphology as induced by the observation of the Hi emission line in the same systems. For Klemola 31, this thesis identifies significant Hi deficiencies and interactions between member galaxies, with notable evidence of tidal interactions between Klemola 31 A and Klemola 31 B as well as ESO400-11 and LEDA2807038; and possible ram-pressure stripping in ESO400-13. The combined analysis of the Hi in emission and absorption indicates the presence of an extraplanar and potential intra-group medium in the group. The UGC439 group was observed in the commissioning phase of the MeerKAT array, revealing contrasting Hi distributions, with the central three galaxies indicating Hi excess while the peripheral galaxies indicating Hi deficiencies. There are two Hi clouds, one close to the central three galaxies and the other to the north. In this case, the observations are consistent with an Hi absorption system from within the disk of a galaxy. This thesis also highlights the necessity for further high spatial and spectral resolution observations to further reveal the intricacies of gas dynamics and its critical role in the life-cycle of galaxies. It serves as an outlook for further studies of the Hi environment of galaxies by combining absorption and emission line studies as first provided by MALS and ultimately by deep Hi surveys with the Square Kilometre Array. This thesis is organised into four chapters. The first chapter details a few concepts and background information about the physics of galaxy evolution. Chapter two talks about Klemola 31 galaxy group, where we start by describing our observation, data reduction and source finding. Thereafter, we explore the Hi morphology and kinematics of this group. In Chapter Three, we turn our attention to UGC439 galaxy group and organise it in a similar manner. A summary and comparison of the two groups is presented in Chapter 4.
Keywords: MeerKAT; Galaxies -- Clusters; Square Kilometre Array; H I region